Mini-Scleral Lenses for Correction of Refractive Errors After Radial Keratotomy. (November 2018) - Chu, Hsiao-Sang; Wang, I-Jong; Tseng, Grace A.; Chen, Wei-Li; Hou, Yu-Chih; Hu, Fung-Rong
Abstract : Objective: To evaluate the factors affecting clinical outcomes of correcting cumulative refractive errors or irregular astigmatism after radial keratotomy (RK) using mini-scleral lenses. Methods: We retrospectively analyzed 36 eyes receiving mini-scleral lenses after RK from July 2011 to June 2016. Analyses included age, refractive errors, best spectacle–corrected visual acuity (BSCVA), best contact lens–corrected visual acuity (BCLCVA), topographic indices, RK treatment zone diameter (TZD), power difference (PrD) within the RK treatment zone, and decentration distance (DD) of the RK treatment zone center. An increase of three lines or more of Snellen visual acuity was considered a successful fitting. Results: Of the eyes fitted with mini-scleral lenses, the BCLCVA (logarithm of the minimum angle of resolution [logMAR] 0.19±0.22) was significantly better than the BSCVA (logMAR 0.47±0.30). Twenty-three patients (64%) had a successful fitting. There was no statistically significant difference between successful and unsuccessful fittings with regard to age, prefitting refractive error, BSCVA, corneal astigmatism, simulated steep/flat K values, surface regularity index, TZD, or PrD. However, successful fittings had better centration of treatment zones with an average DD of 0.54±0.44 mm compared with a DD of 0.92±0.53 mm in the unsuccessfully fitted eyes. In addition, our case series showed that there was a negative impact on fitting outcomes in the presence of small central clear zones resulting from central incisions or scars. Conclusions: Although decentration of the RK treatment zone and small central clear zones were related to less optimal fitting results, mini-scleral lenses are a feasible option to correct cumulative refractive errors and irregular astigmatism in post-RK patients. Abstract : Supplemental Digital Content is Available in the Text.